The ins and outs of calcium signalling in lactation and involution: Implications for breast cancer treatment. (February 2017) - Davis, Felicity M.
Graphical abstract: Abstract: The mammary epithelium is highly responsive to hormonal and non-hormonal signalling cues for physiological growth, function and tissue remodelling. Whilst steroid hormones freely diffuse across the cell membrane to bind to intracellular hormone receptors, cell-impermeable ligands, including many peptide hormones, growth factors and cytokines, bind to receptors on the plasma membrane and relay their message via the specific activation of intracellular signal transduction pathways. A signalling pathway that is indispensable for decoding many extracellular signals into cellular responses is calcium (Ca 2+ ). Changes in the expression of specific Ca 2+ channels, pumps and binding proteins may therefore greatly alter the nature of the cellular response to various growth, morphogenetic and cell death stimuli. This review summarises changes in the expression, localisation and function of key Ca 2+ channels and pumps in mammary epithelial cells during lactation and discusses how this altered Ca 2+ handling may later expose these cells to targeted cell death during post-lactational involution. A greater understanding of the processes regulating the growth, death and regeneration of the mammary epithelium under physiological conditions may provide important insights into the proliferation and survival mechanisms underpinning malignant growth. The therapeutic manipulation of specific calcium signalling pathways in breast cancer cells to control aberrant cell proliferation and/or turnover represents an aim for the future.